Callous-Unemotional Traits Do Not Predict Functional Family Therapy Outcomes for Adolescents With Behavior Problems - Thøgersen, Dagfinn Mørkrid; Bjørnebekk, Gunnar; Scavenius, Christoffer; Elmose, Mette (Frontiers in Psychology, 2021)
Despite the availability of evidence-based treatment models for adolescent behavior problems, little is known about the effectiveness of these programs for adolescents with callous-unemotional (CU) traits. Defined by lack of empathy, lack of guilt, flattened affect and lack of caring, CU traits have been linked to long-term anti-social behavior and unfavorable treatment outcomes and might be negatively related to outcomes in evidence-based programs such as Functional Family Therapy (FFT). This study used a single-group pre-post evaluation design with a sample of 407 adolescents (49.1% female, mean age = 14.4 years, SD=1.9) receiving FFT to investigate whether outcomes in FFT are predicted by CU traits and to what extent reliable changes in CU traits can be observed. The results showed that although CU traits are related to increased problem severity at baseline, they did predicted neither treatment dropout nor post-treatment externalizing behavior and family functioning. CU traits were related to diminished improvement ratings, in particular with respect to parental supervision. Reductions in CU traits were observed across the time of treatment, and these were most profound among adolescents with elevated levels of CU traits at baseline. Further research should investigate whether certain evidence-based treatment components are more suited for adolescents with CU, and if the addition of specific intervention elements for reducing CU-traits could further improve outcomes for this high-risk population.